Ortner's Syndrome: A Comprehensive Review of Etiology, Clinical Presentation, and Management - Donaldo Emiliano Silva López; Sussan Irlanda Méndez Ynostroza; Magda Karina López Saldaña; Sebastián Medina Torres; Mayra Aréchiga López; Karla Valdos Rodríguez (International Journal of Medical Science and Clinical Research Studies, 2024)
Ortner's syndrome, also known as cardiovocal syndrome, is a rare clinical entity characterized by left recurrent laryngeal nerve palsy secondary to cardiovascular pathology. Initially described in the context of left atrial enlargement due to mitral stenosis, the syndrome has since been associated with various cardiac and thoracic abnormalities, including aortic aneurysms, pulmonary hypertension, and congenital heart defects. This review aims to provide an in-depth analysis of Ortner's syndrome, encompassing its etiological factors, pathophysiology, clinical manifestations, diagnostic approaches, and therapeutic strategies. We also discuss the historical evolution of the syndrome's understanding and highlight contemporary advancements in its diagnosis and management. Enhanced awareness and timely recognition of Ortner's syndrome are crucial for appropriate intervention and improved patient outcomes.